7-Chloro-4-[(E)-N `-(4-fluorobenzylidene)hydrazinyl]quinoline monohydrate - de Souza, M.V.N.; Howie, R.A.; Tiekink, E.R.T.; Wardell, J.L.; Wardell, S.M.S.V. (International Union of Crystallography, 2010)
The molecule of the title hydrate, C(16)H(11)ClFN(3)center dot H(2)O, is slightly twisted, as indicated by the dihedral angle of 9.55 (10)degrees formed between the quinoline ring system and the benzene ring. The conformation about the C=N double bond is E, and the amine-H atom is oriented towards the quinoline residue. In the crystal structure, the water molecule accepts an N-H center dot center dot center dot O and makes two O-H center dot center dot center dot N quinoline hydrogen bonds, generating a two-dimensional array in the ab plane, which is further stabilized by C-H center dot center dot center dot O interactions. The most significant contacts between layers are of the type C-H center dot center dot center dot F.